2018
DOI: 10.1063/1.5029893
|View full text |Cite
|
Sign up to set email alerts
|

Resonant intersubband polariton-LO phonon scattering in an optically pumped polaritonic device

Abstract: We report experimental evidence of longitudinal optical (LO) phonon-intersubband polariton scattering processes under resonant injection of light. The scattering process is resonant with both the initial (upper polariton) and final (lower polariton) states and is induced by the interaction of confined electrons with longitudinal optical phonons. The system is optically pumped with a mid-IR laser tuned between 1094 cm -1 and 1134 cm -1 (=9.14 m and =8.82 m). The demonstration is provided for both GaAs/AlGaA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
(43 reference statements)
2
22
0
Order By: Relevance
“…The MQW structures used in this study were initially designed for the demonstration of intersubband polaritons in metal-insulator-metal (MIM) cavities [10,16]. They have been grown by molecular beam epitaxy on Semi-insulating GaAs.…”
Section: Samples Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The MQW structures used in this study were initially designed for the demonstration of intersubband polaritons in metal-insulator-metal (MIM) cavities [10,16]. They have been grown by molecular beam epitaxy on Semi-insulating GaAs.…”
Section: Samples Descriptionmentioning
confidence: 99%
“…Such polaritonic coherent emitter is based on final state stimulation, and it was proposed to exploit longitudinal optical (LO) phonon-polariton interaction as the main spontaneous scattering mechanism. The first study of phonon-polariton scattering was reported several years ago with electrically injected devices [9], and more recently phonon-polariton scattering mediated polaritonic emission was demonstrated under an optical pumping scheme [10]. The threshold intensity for final state stimulation can be estimated using the following expression:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are low enough to be tolerated for longer mid-IR [13]and THz wavelengths [14]. This confinement strategy, that is typically based on Au-Au thermocompression waferbonding, is amply used for active devices such THz lasers [15][16][17] and detectors [17][18][19], but also for mid-IR devices operating in the strong light-matter coupling regime [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Other phenomena that can be studied in the multiple quantum wells is the coupling of the intersubband transitions with light-matter excitations, such as LO phonons. This has been already studied in systems such as GaAs/AlGaAs and InGaAs/AlInAs, 178 where the interaction of LO phonons with the ISBTs in the ultra-strong coupling regime, shows optimistic values for the polariton lasing threshold intensity, revealed to be in the order of 70 kW cm -2 .…”
Section: Future Workmentioning
confidence: 88%